Fullerene-regulated graphene oxide nanosheet membranes with well-defined laminar nanochannels for precise molecule sieving. Issue 45 (30th October 2018) - Tang, Xingyan; Qu, Yan; Deng, Shun-Liu; Tan, Yuan-Zhi; Zhang, Qiugen; Liu, Qinglin
Abstract : Graphene oxide nanosheet membranes with well-defined laminar nanochannels were constructed using functionalized fullerene as a nano-spacer and a crosslinker. The resultant membranes retain good hydrophilicity and have short laminar channels with precise d -spacing from 0.91 to 1.56 nm and excellent sieving selectivity for organic dyes. Abstract : Graphene oxide nanosheets (GONs), featuring atomic thickness, good dispersibility, robustness and high production yield, have attracted great attention in the fabrication of ion and molecule sieving membranes. However, construction of well-defined two-dimensional nanochannels for precise separation of small molecules is still a challenge. Herein, we demonstrate a versatile strategy to construct well-defined laminar nanochannels of GON membranes sized at 1–2 nm for high-efficient molecule separation by introducing functionalized fullerenes (C60 ). Functionalized C60 is not only a well-defined and rigid nanosized fulcrum to precisely construct the laminar nanochannels, but also a crosslinker to produce membranes with excellent structural stability. The resultant membranes retain good hydrophilicity and have short laminar nanochannels with a precise height from 0.91 to 1.56 nm. The membrane with perfect 1.56 nm-high channels has the highest water permeability, which is four orders of magnitude higher than that of the reduced GON membrane, and shows excellent size selectivity for organic dyes. Furthermore, the fabricated membranes display robust mechanical strength and good long-term stability for nanofiltration.